RELATIONSHIP BETWEEN KNOWLEDGE OF REPRODUCTIVE HEALTH WITH THE PREVENTION OF EARLY MARRIAGE IN ADOLESCENT WOMEN IN RW 002 CIBEUTEUNG VILLAGE, UDIK, BOGOR DISTRICT - Simarmata, Agnes Defvi; Hasanah, Uswatun; Rusbandi, Rusbandi; Marsiwi, Andini Restu; Ardi, Ni Bodro; Ningrum, Mita Widya; Fasimi, Rizki Handayani; Nurhaeti, Ade (NURSING ANALYSIS: Journal of Nursing Research, 2025)
According to the World Health Organization adolescents are residents aged 10-19 years, the United Nation Fund for Population Activities (UNFPA) in 2020 the increase in early marriage every year reached 14.2 million, West Java in 2021 is one of the other provinces with a fairly high underage marriage rate of 20.93%. Knowledge is very instrumental in the Prevention of early marriage because with bad knowledge is very influential on adolescents who are at risk of reproductive health. The purpose of this study was to determine the relationship of reproductive health knowledge with the Prevention of early marriage in adolescent girls in RW 002 Cibeuteung Village Udik Bogor regency. This research method uses descriptive analytical research design cross sectional method with a quantitative approach using purposive sampling technique with a population and a sample of 60 respondents, this research instrument uses a questionnaire, the sample criteria are young women aged 15-19 years. The results of the study: univariate: half of respondents have sufficient knowledge of reproductive health, namely 29 respondents 48.3% and more than half of respondents have sufficient prevention of early marriage, namely 38 respondents 63.3%. Bivariate: this is obtained from Spearman rho test results obtained obtained value (p-value 0.000) so that (p-value a 0.05) then ha is accepted. The conclusion of this study is that there is a significant relationship between reproductive health knowledge with the Prevention of early marriage in adolescent girls in RW 002 Village Cibeuteung Udik Bogor regency. This research suggestion is expected to be useful, especially in the community to know more about reproductive health knowledge and Prevention of early marriage.